A Translational Investigation Linking Pharmacological Mechanisms of Drug Toxicity to Clinical Safety Outcomes and Adverse Drug Reactions - Unissa, Maher; Ali, Mohammed (Journal of Pharmacy Practice and Community Medicine, 2026)
Drug toxicity remains a major determinant of Adverse Drug Reactions (ADRs), treatment discontinuation, regulatory restrictions, and patient morbidity, highlighting the limitations of conventional preclinical safety evaluation. Translational pharmacology provides an integrative framework that bridges molecular and cellular mechanisms of toxicity with organ-level dysfunction and clinically observable safety outcomes. This review examines the mechanistic basis of drug-induced toxicity, emphasizing on-target and off-target pharmacological effects, metabolic bioactivation and reactive metabolite formation, immune-mediated hypersensitivity, and downstream cellular stress pathways. These molecular initiating events are traced through tissue injury processes to organ-specific clinical manifestations, including hepatotoxicity, cardiotoxicity, nephrotoxicity, neurotoxicity, and cutaneous reactions, ultimately culminating in clinically classified adverse drug reactions. The influence of patient-specific determinants such as genetic polymorphisms, age, comorbidities, and polypharmacyis discussed to explain interindividual variability in toxicity risk and ADR susceptibility. Furthermore, the role of pharmacovigilance systems and real-world evidence is explored as part of a bidirectional translational model, wherein clinical safety signals inform mechanistic understanding and guide regulatory decision-making. Emerging approaches, including systems pharmacology, in silico modeling, and artificial intelligence-driven prediction platforms, are highlighted for their potential to enhance mechanism-based safety assessment. Understanding these mechanistic-to- clinical linkages is essential for improving drug development, advancing precision medicine, strengthening regulatory science, and ultimately enhancing patient safety.
Keywords: Translational pharmacology; Drug toxicity; Adverse drug reactions; Clinical safety; Pharmacovigilance; Pharmacogenomics